Remove the Wounds in the City (Policy) for Lepers in Surabaya in the 19th Century - Moordiati Moordiati (MOZAIK HUMANIORA, 2020)
This article aims to discuss about the treatment of people with leprosy (leprosy) in Surabaya during the nineteenth century.  The maltreatment can not be ignored since their existence was never really desirable  in the city, let alone the many stigmas that had already been attached to them. It is not unusual if people had the desire to  "remove" them from the city.  But apparently this action also not an easy matter to bring about, especially amid the presence of a wide range of arguments and the final decision as to whether or not "deletion" ( forced exile) supported the removal of  those lepers that occurred during this period.Keywords Lepers - Surabaya - policy - deletion - forced exile.